Odpowiedź :
Odpowiedź:
5 i 6/10 + 8/10 = 5 i 14/10 = 6 i 4/10 = 6 i 2/5
4 i 2/5 + 1 i 4/5 = 5 i 6/5 = 6 i 1/5
1/3 + 1/2 = 2/6 + 3/6 = 5/6
1/7 + 2/3 = 3/21 + 14/21 = 17/21
1 i 7/8 + 3 i 1/3 = 1 i 21/24 + 3 i 8/24 = 4 i 29/24 = 5 i 5/24
3 i 3/5 + 2 i 1/2 = 3 i 6/10 + 2 i 5/10 = 5 i 11/10 = 6 i 1/10
Szczegółowe wyjaśnienie:
e)
[tex]5\frac{6}{10} + \frac{8}{10} = \frac{56}{10} + \frac{8}{10} = \frac{56 + 8}{10} = \frac{64}{10} = 6 \frac{4}{10} = 6 \frac{2}{5}[/tex]
f)
[tex]4\frac{2}{5} +1\frac{4}{5} = 4 + 1 + \frac{2}{5} + \frac{4}{5} = 4 + 1 + \frac{2+4}{5} =4 + 1 + \frac{6}{5} = 4 + 1 + 1\frac{1}{5} = 6\frac{1}{5}[/tex]
e)
[tex]\frac{1}{3} + \frac{1}{2} =\frac{1}{3} * \frac{2}{2} + \frac{1}{2} * \frac{3}{3} = \frac{2}{6} + \frac{3}{6} = \frac{5}{6}[/tex]
f)
[tex]\frac{1}{7} + \frac{2}{3} =\frac{1}{7} * \frac{3}{3} + \frac{2}{3} * \frac{7}{7} = \frac{3}{21} + \frac{14}{21} = \frac{17}{21}[/tex]
e)
[tex]1\frac{7}{8} + 3\frac{1}{3} = \frac{15}{8} + \frac{10}{3} = \frac{15}{8} * \frac{3}{3} + \frac{10}{3} * \frac{8}{8} = \frac{45}{24} + \frac{80}{24} = \frac{125}{24} = 5\frac{5}{24}[/tex]
f)
[tex]3\frac{3}{5} + 2\frac{1}{2} = \frac{18}{5} + \frac{5}{2} = \frac{18}{5} * \frac{2}{2} + \frac{5}{2} * \frac{5}{5} = \frac{36}{10} + \frac{25}{10} = \frac{61}{10} =6\frac{1}{10}[/tex]